Environmentally Based STAD Type Cooperative Learning Model Improves Mathematics Learning Outcomes - I Made Ayada; I Made Tegeh (Jurnal Ilmiah Sekolah Dasar, 2023)
Mathematics is one of the main subjects at the primary education level, which most dislike does not. Mathematics is considered difficult, and many formulas have to be memorized, as well as many complicated calculations. This research aims to determine whether the STAD environment-based cooperative learning model influences the mathematics learning outcomes of fifth-grade elementary school students. This research is quasi-experimental with a nonequivalent post-test-only control group design. The population in this study was 263 students. The sample for this research was 29 fifth-grade elementary school students in the experimental class and 25 students in the control class. The sample selection for this research used random sampling techniques. Data on mathematics learning outcomes was collected using a multiple-choice test. The data obtained were analyzed using the t-test. The research results show that significant differences indicate that the STAD learning model affects student learning outcomes. There is a significant difference in the value of student learning outcomes between the students who took part in learning using the STAD learning model and those who took part in learning activities using the conventional learning model. The research conclusion is that the environment-based STAD learning model influences mathematics learning outcomes. The research results prove that the STAD learning model can be applied in elementary schools to improve student learning outcomes.